Upaya Penerapan Sanksi Administratif Dan Perizinan Sebagai Pembatasan Terhadap Kebebasan Bertindak - Nasution, Bahder Johan (UIN Sunan Kalijaga, 2014)
Permit is defined as an exception to everything that principally prohibited things or not to do, so granting permission is an exception to the ban. The application of administrative sanctions in a permit is a limitation of freedom to act. Permit as a legal instrument to restrict the freedom of action for a person should rely on the rules of law and principles of good governance. The application of administrative sanctions in a licensing function to organize, control and direct someone freedom of action to act in accordance with the rule of law.